Analisis Human Security dalam Resolusi Dewan Keamanan Persatuan Bangsa-Bangsa (DK PBB) No. 2334 Tahun 2016 - Hata, Zulva Talida; wijayanti, sri (POLITEA, 2022)
UN Security Council resolution no. 2334 is issued to resolve the conflict between Palestine and Israel. This resolution contains orders for Israel to halt the expansion of settlements and to stop the demolition of Palestinian homes. Basically, the resolution aims to defuse conflict and to create peace in the region. The expected peaceful situation will affect security for humans. Therefore, this paper will analyze UN Security Council resolution no. 2334 with a human security approach. This paper finds that UN Security Council resolution 2334 fulfilled the indicator of human security approach because the resolution urges the parties to comply with the laws of Geneva Convention IV, international humanitarian law, the opinion of the International Court of Justice, the Quartet Roadmap, as well as many previous resolutions. All international instruments that are mentioned are focused on discussion to protect human in economic, food, health, environmental, personal, community, political and human rights. However, in practice, this resolution met many obstacles, and even tended to be ignored by Israel. This paper uses a descriptive qualitative method with data collection techniques carried out through a literature review.